SOSIALISASI PEMBUATAN ECOENZYM: SEBAGAI SOLUSI PRAKTIS UNTUK MENGURANGI LIMBAH ORGANIK - Galih Ikhsan Satriaji; Roby Andrey Sihotang; Nurwinda Haliza; Fadilla Ramadhani; Tahnia Arsylia; Aisyah Amaliyah Dzikra Harahap; Elsa Shafira; Meliani Putri; Maya Dola Purba; Sophia El Zahra (JURNAL PENGABDIAN MANDIRI, 2024)
Organic waste is one of the main problems in Teluk Sungkai Village, Kuala Cenaku District, Indragiri Hulu Regency. Suboptimal waste handling often causes environmental problems, such as pollution and the spread of disease. Ecoenzym, a liquid fermented organic waste with sugar and water, has been proven to be an environmentally friendly and economical solution. This article evaluates the effectiveness of socialization of ecoenzyme-based waste processing in reducing organic waste in Teluk Sungkai Village. Through a participatory approach, the public is educated about the benefits and process of making ecoenzymes. The results showed an increase in environmental awareness and a significant reduction in the volume of organic waste in the village.